Association of Dandy-Walker Malformation and Neurocutaneous Melanosis in a Newborn: A Case Report - Azamolmolouk Elsagh; Ali Reza Jashni Motlagh (Mashhad University of Medical Sciences, 2019)
Background: This case report presents a very rare Dandy-Walker malformation (DWM) in association with a sporadic condition characterized by congenital melanocytic nevi and melanocytic thickening of the leptomeninges called Neurocutaneous melanosis (NCM). The DWM is a rare congenital disorder characterized by enlarged posterior fossa and a cystic enlargement of the fourth ventricle with cerebellar vermis dysgenesis. This association is a very rare complex, and this is another rare case to be reported in the literature. Case report: A full-term newborn was presented with tachypnea at birth whose hydrocephalous was reported prenatally. The magnetic resonance imaging and cerebrospinal fluid immunohistochemistry confirmed leptomeningeal melanosis. After documenting findings by skin biopsy, we decided to report this case. Diagnosis and treatment for such disease entity are discussed in this report. Conclusion: Even without malignant transformation, the prognosis is poor after symptomatic progression of the NCM resulting from either mass effect in the central nervous system or hydrocephalus. We reported this case in order to increase the knowledge of pediatric physicians to diagnose this combined situation.